MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIK SISWA SMP DENGAN PENDEKATAN KONTEKSTUAL - Muhamad Yadin; Euis Eti Rohaeti; Luvy Sylviana Zanthy (IKIP Siliwangi, 2019)
This investigate is motivated by the low ability to comprehend the mathematical concepts of SMP students in KBB, so a learning approach is needed to decipher these problems. Alternative approaches are applied, namely the contextual approach. The method make use of in this investigate is an experimental method with a control group design pretest posttest. The population in this research were all junior high schools in KBB while the school sample was Kahuripan Lembang Middle School which was chosen based on school randomization. Sample class were taken randomly from the 4 classes of class 7 of Kahuripan Lembang Middle School, class 7-2 as the tentative class and class 7-4 as the control class. The tentative class uses contextual learning while the ordinary learning control class. The reason for taking class VII is because with deliberation in the semester one there are topics in the Triangle and Quadrangle that will be used in the study. The instrument in this investigation was a package of five test questions. The researcher can conclude that the achievement and repair of the capability of understanding The mathematical concept of SMP students who use a contextual approach is better than those using ordinary learning.